An immobilized symmetrical bis-(NHC) palladium complex as a highly efficient and recyclable Suzuki–Miyaura catalyst in aerobic aqueous media. Issue 2 (14th December 2016) - Begum, Tahshina; Mondal, Manoj; Borpuzari, Manash Protim; Kar, Rahul; Kalita, Golap; Gogoi, Pradip K.; Bora, Utpal
Abstract : A novel palladium-silica complex was prepared and characterized. This complex is a highly efficient and easily recyclable catalyst for Suzuki–Miyaura cross-coupling reaction under mild aqueous conditions, and can be reused efficiently up to 6 consecutive runs. Abstract : A bis-N-heterocyclic carbene (NHC) functionalized with chloropropyltriethoxysilane over silica was used to synthesize a well-defined immobilized palladium complex. This complex is a suitable and easily retrievable catalyst for Suzuki–Miyaura cross-coupling reactions under mild aqueous conditions. Excellent yields and conversions were obtained with low palladium loadings (down to 0.03 mol% Pd). The catalyst can be reused up to six cycles without the loss of its activity. The catalytic role of the NHC complex of palladium during coupling between bromobenzene and phenylboronic acid was investigated theoretically. The oxidative addition step is predicted to be endothermic in agreement with the experimental conditions.